Tissue Damage Caused by Diclofenac Intramuscular Injection: The Nicolau Syndrome - Anees, Afzal; Hassan, Yaqoob; Motiwala, Zainab Yusufali; Khan, Isna Rafat (Ibnosina Journal of Medicine and Biomedical Sciences, 2023)
Introduction Nicolau syndrome is an extremely rare complication following intramuscular administration of drugs leading to tissue damage and necrosis.Case Report In this case, the patient received the injection from an untrained quack surgeon (Jarrah) due to an improper intramuscular injection technique. A 45-year-old female complained of pain and blackish discoloration of the skin over the left buttock after receiving an intramuscular diclofenac injection.4 The patient was managed by administering intravenous antibiotics and analgesics, followed by surgical debridement. Flap reconstruction was done after granulation tissue formation.Conclusion Healthcare should be sought from appropriately trained and licensed professionals. Patients should be well educated on this. Pain, erythema, and discoloration should be recognized as red flags of the Nicolau syndrome so that it can be addressed promptly to avoid complications.
Keywords: injection; diclofenac; Nicolau syndrome; intramuscular